Exploring the culture of Open Innovation : towards an altruistic model of economy - Formica, Piero; Curley, Martin (Emerald Publishing Limited, 2018)
Acclaimed entrepreneurship and innovation scholar Piero Formica, along with a strong and diverse cast of international contributors, explore the world of Open Innovation in this volume. Tackling new developments in the field, the authors examine altruism and the role of openness to unorthodox and unconventional experimentation as the newest arena to create modern knowledge resources and entrepreneurial ventures.